Biofilm formation of two genetically diverse Staphylococcus aureus isolates under beta-lactam antibiotics - Liang, Jinglong; Huang, Teng Yi; Mao, Yuzhu; Li, Xuejie (Frontiers in Microbiology, 2023)
Purpose: Our aim was to evaluate the genotypes associated with drug resistance and the formation of biofilm in two S. aureus isolates, 10379 and 121940, identified from the First Affiliated Hospital of Guangzhou Medical University, as well as to study the effect of low concentrations of beta-lactam antibiotics on biomass content and biofilm viability. Methods: Biofilm formation and methicillin resistance genes were tested using PCR and multiplex PCR. PCR was combined with bioinformatics analysis to detect multilocal sequence typing (MLST) and SCCmec types. The crystal violet (CV) test and XTT were used to detect biomass content and biofilm activity. Antibiotic susceptibility was tested using a broth dilution method. Results: Strain 10379 carried the icaD, icaBC, and MRSA genes, not the icaA, atl, app, agr genes, and MLST and SCCmec typing was ST45 and IV, respectively. Strain 121940 carried the icaA, icaD, icaBC, atl, and agr genes, not the aap gene, and MLST and SCCmec are typed as ST546 and IV respectively. This suggested that strains 10379 and 121940 were genotypically very different. Two S. aureus isolates, 10379 and 121940, showed resistance to beta-lactam antibiotics, penicillin, ampicillin, meropenem, streptomycin and kanamycin, some of which promoted the formation of biofilm and biofilm viability at low concentrations. Conclusion: Despite the large differences in the genetic background of S. aureus 10379 and 121940, some sub-inhibitory beta-lactam antibiotics are able to promote biomass and biofilm viability of two isolates.